Three-dimensional simulations of clump formation in stellar wind collisions. Issue 1 (14th January 2020) - Calderón, D; Cuadra, J; Schartmann, M; Burkert, A; Prieto, J; Russell, C M P
ABSTRACT: The inner parsec of our Galaxy contains tens of Wolf–Rayet stars whose powerful outflows are constantly interacting while filling the region with hot, diffuse plasma. Theoretical models have shown that, in some cases, the collision of stellar winds can generate cold, dense material in the form of clumps. However, their formation process and properties are not well understood yet. In this work, we present, for the first time, a statistical study of the clump formation process in unstable wind collisions. We study systems with dense outflows (${\sim }10^{-5}\rm \ M_{\odot }\ yr^{-1}$ ), wind speeds of 500–$1500\rm \ km\ s^{-1}$, and stellar separations of ∼20–$200\rm \ au$ . We develop three-dimensional high-resolution hydrodynamical simulations of stellar wind collisions with the adaptive-mesh refinement grid-based code ramses . We aim at characterizing the initial properties of clumps that form through hydrodynamic instabilities, mostly via the non-linear thin-shell instability (NTSI). Our results confirm that more massive clumps are formed in systems whose winds are close to the transition between the radiative and adiabatic regimes. Increasing either the wind speed or the degree of asymmetry increases the dispersion of the clump mass and ejection speed distributions. Nevertheless, the most massive clumps are very light (∼10 −3 –$10^{-2}\rm \ M_{\oplus }$ ), about three orders of magnitude less massive than theoretical upper limits. Applying these results to the Galactic Centre, we find that clumps formed through the NTSI should not be heavy enough either to affect the thermodynamic state of the region or to survive for long enough to fall on to the central supermassive black hole.